Hubungan Status Pemberian ASI dan Makanan Pendamping ASI terhadap Stunting Anak Usia 1-2 Tahun di Kecamatan Cisolok Kabupaten Sukabumi Tahun 2015 - Heni Haryani; Yuni Susanti Pratiwi; Kusnandi Rusmil; Meita Dhamayanti; Farid Husin; Firman F Wiranatakusumah (STIKes Karsa Husada Garut, 2016)
Stunting is a condition in which a child’s height or length is less than two deviation standard based on the 2006 World Health Organization’s growth chart. In Indonesia, most of stunting is caused by chronic malnutrition. Children of age 1-2 years old are vulnerable to malnutrition because at this age most of them start to be weaned and introduced to complementary food. The study aims to find the correlation between breasfeeding and complementary food with stunting among 1-2 year old children at Cisolok District, Sukabumi Regency, 2015. The Study was observasional-analytical, a case-control study, carried out from January 1 – February 28, 2016. Subjects were selected with consecutive sampling, including 1-2 year old children with stunting along with their mothers residing at Cisolok District, Sukabumi Regency. Data on the lengths of children were taken by the researcher in the local Integrated Service Post (Indonesia, Posyandu), and there was also a questionnaire of breastfeeding history and an SQ-FFQ filled out by nutritionists directly at the subjects’s houses. The data were analyzed with chi square, fisher’s exact, and linear regression tests with the level of significanceor (p<0.05). The results show that out of 108 subjects, there were 36 cases and 72 controls. The exclusive brestfeeding, breastfeeding after six months old, age at first introduction to compelentary food, and energy intake did not correlate with stunting (p>0.05). The protein intake correlated with stunting (p=0.009) with weak correlation coefficients (r=0.284). In conclusions, there was not correlation between breastfeeding (exclusive breastfeeding and breastfeeding after six months old), the age at first introduction to compelentary food, and energy intake with stunting among 1-2 year old children at Cisolok District, Sukabumi Regency, 2015. There was correlation between protein intake with stunting among 1-2 year old children at Cisolok District, Sukabumi Regency, 2015.